Additions to the description of Paroplocephalus atriceps (Serpentes: Elapidae) with a discussion on pupil shape in it and other Australian snakes - Bush, Brian (Zootaxa, 2017)
Morphometric data on an additional twelve individuals of Paroplocephalus atriceps Storr are included enlarging Keogh et al.’s 2000 description of the genus and further verifying its affinities with Hoplocephalus. Included are comments on its venom and observations confirming arboreality and although primarily nocturnal, it includes some diurnal activity. Various authors have erroneously suggested it has vertically elliptic pupils but they are round. During an examination of snake’s eyes, it was found that several additional species have pupils that require re-describing, especially Suta fasciata Rosen, S. punctata Boulenger and Echiopsis curta Schlegel, all of which include individuals with round pupils. A standardised description is suggested for each of the three common pupil shapes in snakes as narrow elliptic where dilation and constriction is lateral or vertical only, wide elliptic where dilation and constriction is both lateral and vertical, and round where any dilation and constriction is equidistant from the centre around the pupil’s circumference.